How does integrated knowledge translation (IKT) compare to other collaborative research approaches to generating and translating knowledge? Learning from experts in the field - Nguyen, Tram; Graham, Ian D; Mrklas, Kelly J; Bowen, Sarah; Cargo, Margaret; Estabrooks, Carole A; Kothari, Anita; Lavis, John; Macaulay, Ann C; MacLeod, Martha; Phipps, David; Ramsden, Vivian R.; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Research funders in Canada and abroad have made substantial investments in supporting collaborative research approaches to generating and translating knowledge as it is believed to increase knowledge use. Canadian health research funders have advocated for the use of integrated knowledge translation (IKT) in health research, however, there is limited research around how IKT compares to other collaborative research approaches. Our objective was to better understand how IKT compares with engaged scholarship, Mode 2 research, co-production and participatory research by identifying the differences and similarities among them in order to provide conceptual clarity and reduce researcher and knowledge user confusion about these common approaches. Methods We employed a qualitative descriptive method using interview data to better understand experts’ perspectives and experiences on collaborative research approaches. Participants’ responses were analysed through thematic analysis to elicit core themes. The analysis was centred around the concept of IKT, as it is the most recent approach; IKT was then compared and contrasted with engaged scholarship, Mode 2 research, co-production and participatory research. As this was an iterative process, data triangulation and member-checking were conducted with participants to ensure accuracy of the emergent themes and analysis process. Results Differences were noted in the orientation (i.e. original purpose), historical roots (i.e. disciplinary origin) and partnership/engagement (i.e. role of partners etc.). Similarities among the approaches included (1) true partnerships rather than simple engagement, (2) focus on essential components and processes rather than labels, (3) collaborative research orientations rather than research methods, (4) core values and principles, and (5) extensive time and financial investment. Core values and principles among the approaches included co-creation, reciprocity, trust, fostering relationships, respect, co-learning, active participation, and shared decision-making in the generation and application of knowledge. All approaches require extensive time and financial investment to develop and maintain true partnerships. Conclusions This qualitative study is the first to systematically synthesise experts’ perspectives and experiences in a comparison of collaborative research approaches. This work contributes to developing a shared understanding of collaborative research approaches to facilitate conceptual clarity in use, reporting, indexing and communication among researchers, trainees, knowledge users and stakeholders to advance IKT and implementation science.